Choline PET/CT in recurrent prostate cancer - Detti, Beatrice; Carnevale, Maria Grazia; Lucidi, Sara; Burchini, Luca; Caini, Saverio; Orsatti, Carolina; Bertini, Niccolò; Roghi, Manuele; di Cataldo, Vanessa; Fondelli, Simona; Ingrosso, Gianluca; Francolini, Giulio; et al. (Frontiers in Oncology, 2023)
Purpose: Biochemical recurrence (BR) occurs in up to 40% of patients with prostate cancer (PCa) treated with primary radical prostatectomy (RP). Methods/Patients: Patients with recurrent and non-metastatic prostate cancer (nmPCa), who were assessed with choline-PET/CT were included in the analysis. Based on imaging results, the following therapeutic strategies were chosen: radiotherapy to the prostatic bed, androgen deprivation therapy (ADT), chemotherapy or Stereotactic Radiotherapy (SBRT) to either pelvic lymph nodes or distant metastases. We assessed the impact of age, PSA levels, Gleason Score (GS) and adjuvant therapy on oncological outcomes. Results: Data from 410 consecutive nmPCa patients with BR who underwent RP as primary treatment were analyzed. 176 (42.9%) patients had a negative choline-PET/CT, 234 (57.1%) patients resulted positive. At multivariate analysis, only chemotherapy and PSA at recurrence were significant independent prognostic factors on overall survival (OS). In the PET-positive subgroup, the number of relapses, PSA post-prostatectomy and chemotherapy impacted on OS. PSA (post-surgery and at recurrence) affected Progression-Free Survival (PFS) at univariate analysis. At multivariate analysis, GS, the number of relapse sites, PSA (post-surgery and at the recurrence) were significant prognostic factors for Disease-Free Survival (DFS). Conclusion: Choline-PET/CT provides better accuracy than conventional imaging for assessment of nmPCa with BR after prostatectomy, thereby enabling salvage strategies and improving quality of life.